The Qur'ān's Legal Culture The Didascalia Apostolorum as a Point of Departure - Zellentin, Holger Michael (Mohr Siebeck, 2023)
The Qur'ān, emphasizing ritual purity and the role of Jesus as giver of God's positive law, preserves aspects of an earlier Jesus movement that most Christian groups diluted or rejected. The Didascalia Apostolorum, a late ancient church order, records a significant number of the laws promulgated in the Qur'ān, but does not fully endorse them when it comes to purity. Likewise, the Didascalia' legal narratives about the Israelites and about Jesus, as well as the legal and theological vocabulary of the Syriac (Eastern Christian Aramaic) version of the Didascalia, recurrently show kinship with the Arabic Qur'ān, amplifying the apparent affinities between the two texts. The Qur'ān, however, is not "based" on the Didascalia in any direct way; detailed comparison of the two documents illustrates the absence of textual influence in either direction. Both texts should rather be read against the background of the practices and the oral discourse shared by their respective audiences: a common legal culture. In this volume, Holger M. Zellentin offers new insights into Late Antique Judaism and Christianity, into the continuity of Judaeo-Christian law and narrative within Jewish and Christian mainstream communities past the fourth century, and into the community that the Qur'ān first addressed. Understanding how the Qur'ān parts ways with contemporaneous forms of Christianity and Judaism, both in the initial and in subsequent phases of the internal development of its legal culture, allows for a more precise appreciation of its message.